Doping Free and Amorphous NiOx Film via UV Irradiation for Efficient Inverted Perovskite Solar Cells - Lian, Qing; Wang, Peng‐lai; Wang, Guoliang; Zhang, Xian; Huang, Yulan; Li, Dongyang; Mi, Guojun; Shi, Run; Amini, Abbas; Zhang, Liang; Cheng, Chun (Advanced science, 2022)
High crystallization and conductivity are always required for inorganic carrier transport materials for cheap and high‐performance inverted perovskite solar cells (PSCs). High temperature and external doping are inevitably introduced and thus greatly hamper the applications of inorganic materials for mass production of flexible and tandem devices. Here, an amorphous and dopant‐free inorganic material, Ni3+‐rich NiOx, is reported to be fabricated by a novel UV irradiation strategy, which is facile, easily scaled‐up, and energy‐saving because all the processing temperatures are below 82 ℃. The as‐prepared NiOx film shows highly improved conductivity and hole extraction ability. The rigid and flexible PSCs present the champion efficiencies of 22.45% and 19.7%, respectively. This work fills the gap of preparing metal oxide films at the temperature below 150 °C for inverted PSCs with the high efficiency of >22%. More importantly, this work upgrades the substantial understanding about inorganic materials to function well as efficient carrier transport layers without external doping and high crystallization. Fabrication of effective inorganic hole transport films at low temperature is crucial to move perovskite solar cells one step closer to mass production and then commercialization. Here, the authors report a photochemistry method to synthesize NiOx hole transport layer for perovskite solar cells with a champion performance of 22.45%.